-9-3x=-39

Simple and best practice solution for -9-3x=-39 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -9-3x=-39 equation:


Simplifying
-9 + -3x = -39

Solving
-9 + -3x = -39

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '9' to each side of the equation.
-9 + 9 + -3x = -39 + 9

Combine like terms: -9 + 9 = 0
0 + -3x = -39 + 9
-3x = -39 + 9

Combine like terms: -39 + 9 = -30
-3x = -30

Divide each side by '-3'.
x = 10

Simplifying
x = 10

See similar equations:

| x+2-8x=-3(x-5)-(6x+5) | | -30+6y=-18 | | sqrt(x+48)-sqrt(x-16)=4 | | 2*2*3= | | h(x)=5x-9 | | 21=-3/8x | | -3*5+6y=-18 | | x/17=-34+24 | | 3x^(7/3)-18 | | 2(w-2)=-6w+20 | | 2(8+x)=23 | | 87=3y | | 12+0.5x+0.25y=20 | | x+(x+2)=9 | | 6x-2+2x+12+5x-9=180 | | 13x+17y=3 | | 11(x-1)=5x+25 | | 3x^7/3-18 | | 20+2h-9=2h+11 | | 21-9=s | | 3(5)=2(8) | | 2-p=6-2(p+5) | | -5v-28=8(v+3) | | 5g+3+2g=7g+15 | | x/1=-34+24 | | 6x-3=2x-11 | | Z+3=-6 | | 2-12=z/-5 | | 7v-43=5(v-7) | | 7x-3x+3+7=26 | | 2(-8k+6)=12 | | x^2+x-8=2x |

Equations solver categories